THE MESOZOIC-CENOZOIC BOUNDARY: PALEOMAGNETIC CHARACTERISTIC - Pechersky D.M.; Garbuzenko A.V. (My University, 2005)
The purpose of this paper is to consider the behavior of the geomagnetic field in the vicinity of the Mesozoic-Cenozoic (Mz-Kz) boundary, in particular, of the paleointensity and polarity of the field, the frequency of geomagnetic polarity reversals, the total magnitude of the field direction variations, and the behavior of the magnetic susceptibility of oceanic sediments in the vicinity of the Mz-Kz boundary. As to these paleomagnetic events, worthy of mention is the change in the variation conditions at the Mesozoic-Cenozoic boundary. It is global growth of the average variation magnitude from 8°-8.5°\ in the Late Cretaceous to 11.5o in the Early Cenozoic. The global character of this event suggests a general change in the generation of the geomagnetic field direction variations in the vicinity of the Mz-Kz boundary. A change in the Earth core conditions, causing the reversals of the geomagnetic field, began at ~80 Ma, that is, notably earlier than the Mz-Kz boundary, and, hence, was not associated directly with this boundary, nor with the generation of variations in the geomagnetic field direction. Some local changes in the variations of the magnetic field direction were associated with the formation of plumes near the core-mantle boundary, yet, the plumes have originated 20-40 million years prior to the Mz-Kz boundary. As follows from the examination of sequences of oceanic sediments (DSDP and ODP data), the Mz-Kz boundary is often, but not necessarily, marked by a peak of magnetic susceptibility ( k -peak), i.e. that is not a characteristic feature of the Mz-Kz boundary. The accumulation of magnetic materials in the sediments lasted from a few dozens of thousand years (more common estimates) to hundreds of thousand years. And, where this interval is observed, it does include the Mz-Kz biostratigraphic boundary, except for very rare cases. The Mz-Kz biostratigraphic boundary is always restricted to the C29r chron, but its position varies as a function of its paleolatitude, amounting to about 0.7 Myr. The highest k -peak values are close to the epicenters of active plumes, but high k -peaks have been found far from the plumes.
Keywords: MESOZOIC-CENOZOIC BOUNDARY; GEOMAGNETIC FIELD; PALEOINTENSITY; Mesozoic::Cretaceous; Мезозой::Меловая